2023
DOI: 10.1093/eurheartjsupp/suad072
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of coronary revascularization to recover the contractility of the dysfunctional heart?

Abstract: Coronary artery disease is the predominant aetiology of heart failure and left ventricular dysfunction in industrialized countries. The pathophysiological substrate of hibernating myocardium constitutes the conceptual target of coronary revascularization by coronary artery bypass graft (CABG) or coronary angioplasty or percutaneous coronary intervention (PCI). Studies, mainly observational, conducted in the past have demonstrated a prognostic benefit of CABG on survival. These findings were confirmed by the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The so called no-reflow phenomenon is mainly attributed to coronary microvascular dysfunction that includes impaired vasomotor function, extensive microvascular injury with microvascular obstruction, inflammation and hemorrhage following AMI and reperfusion therapy. Furthermore, the ischemic myocardium undergoes structural and functional remodeling due to stunned and hibernating states [ 34 ]. Stunning is referred to the myocardium that is transiently ischemic and displays contractile dysfunction, which ultimately recovers early after restoration of normal resting blood flow.…”
Section: Pathophysiologic Benefits Of Revascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The so called no-reflow phenomenon is mainly attributed to coronary microvascular dysfunction that includes impaired vasomotor function, extensive microvascular injury with microvascular obstruction, inflammation and hemorrhage following AMI and reperfusion therapy. Furthermore, the ischemic myocardium undergoes structural and functional remodeling due to stunned and hibernating states [ 34 ]. Stunning is referred to the myocardium that is transiently ischemic and displays contractile dysfunction, which ultimately recovers early after restoration of normal resting blood flow.…”
Section: Pathophysiologic Benefits Of Revascularizationmentioning
confidence: 99%
“…Prolonged myocardial hibernation may progress to necrosis, limiting functional recovery after revascularization. Extent of viability is also important, and several studies have shown that at least 25% to 30% of dysfunctional myocardium needs to be viable for improvement in LVEF after revascularization, with the except of extensively remodeled and dilated ventricles which could not recover after revascularization even in the presence of viable areas [ 34 , 35 , 36 ].…”
Section: Pathophysiologic Benefits Of Revascularizationmentioning
confidence: 99%
“…Myocardial revascularization may be considered in patients with left ventricular (LV) systolic dysfunction and appropriate coronary anatomy to improve disease prognosis and alleviate ischemia by addressing the pathophysiological substrate of hibernating myocardium [2,3]. It is noteworthy that patients with LV systolic dysfunction are typically excluded from randomized clinical trials (RCTs) comparing treatment modalities for chronic CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a scarcity of publications focused on studying the optimal strategies for this specific patient group. Hence, the majority of guidelines are based on observational studies and expert opinions [3,4].…”
Section: Introductionmentioning
confidence: 99%